Individualised Exercise Training Enhances Antioxidant Buffering Capacity in Idiopathic Pulmonary Fibrosis - Tim J. M. Wallis; Magdalena Minnion; Anna Freeman; Andrew Bates; James M. Otto; Stephen A. Wootton; Sophie V. Fletcher; Michael P. W. Grocott; Martin Feelisch; Mark G. Jones; Sandy Jack (Antioxidants, 2023)
Exercise training is recommended for patients with idiopathic pulmonary fibrosis (IPF); however, the mechanism(s) underlying its physiological benefits remain unclear. We investigated the effects of an individualised aerobic interval training programme on exercise capacity and redox status in IPF patients. IPF patients were recruited prospectively to an 8-week, twice-weekly cardiopulmonary exercise test (CPET)-derived structured responsive exercise training programme (SRETP). Systemic redox status was assessed pre- and post-CPET at baseline and following SRETP completion. An age- and sex-matched non-IPF control cohort was recruited for baseline comparison only. At baseline, IPF patients (n = 15) had evidence of increased oxidative stress compared with the controls as judged by; the plasma reduced/oxidised glutathione ratio (median, control 1856 vs. IPF 736 p = 0.046). Eleven IPF patients completed the SRETP (median adherence 88%). Following SRETP completion, there was a significant improvement in exercise capacity assessed via the constant work-rate endurance time (+82%, p = 0.003). This was accompanied by an improvement in post-exercise redox status (in favour of antioxidants) assessed via serum total free thiols (median increase, +0.26 μmol/g protein p = 0.005) and total glutathione concentration (+0.73 μM p = 0.03), as well as a decrease in post-exercise lipid peroxidation products (−1.20 μM p = 0.02). Following SRETP completion, post-exercise circulating nitrite concentrations were significantly lower compared with baseline (−0.39 μM p = 0.04), suggestive of exercise-induced nitrite utilisation. The SRETP increased both endurance time and systemic antioxidant capacity in IPF patients. The observed reduction in nitrite concentrations provides a mechanistic rationale to investigate nitrite/nitrate supplementation in IPF patients.